#TITLE_ALTERNATIVE# - MARAMIS (NIM 13204061), HARIYADI
This final project implements an algorithm that could exploit the interblock correlation in the index domain. The algorithm encodes the current index with a search order that corresponds to previous indices in a predefined search path. With this method, the correlation between indices in index map could be exploited better. The system is implemented using a java programming language and tested with an 8 bit index map from VQ encoder. The result shows that the algorithm could improve the compression ratio to 35% compare to Huffman with 30%, reduce the bitrate to 6,4 bpp from Huffman 7,13 and need less time to do an encode and decode process.